2017
DOI: 10.3139/217.3272
|View full text |Cite
|
Sign up to set email alerts
|

Design Guidelines to Balance the Flow Distribution in Complex Profile Extrusion Dies

Abstract: In this work a novel methodology to balance the flow distribution in complex extrusion dies is proposed. For this purpose, the profile cross section geometry is divided into simpler geometries (L and T shaped profiles), which are balanced with a surrogate model obtained by a detailed numerical study. The numerical simulations are performed considering the non-isothermal flow of Bird-Carreau inelastic fluids, and the numerical computations are performed with a solver implemented in OpenFOAM computational librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…At the solid die wall, the no-slip (tangential velocity is zero) and no-penetration (normal velocity is zero) conditions are imposed for velocity, zero-gradient pressure, and a fixed value temperature. At the free-surface, the kinematic condition, Equation (8), and the dynamic condition, Equations ( 10) and (11), are imposed for pressure and velocity, along with natural convection, Equation (12), for temperature. Finally, the outflow plane is taken sufficiently far downstream of the die exit so that the flow is uniform.…”
Section: Problem Domain and Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the solid die wall, the no-slip (tangential velocity is zero) and no-penetration (normal velocity is zero) conditions are imposed for velocity, zero-gradient pressure, and a fixed value temperature. At the free-surface, the kinematic condition, Equation (8), and the dynamic condition, Equations ( 10) and (11), are imposed for pressure and velocity, along with natural convection, Equation (12), for temperature. Finally, the outflow plane is taken sufficiently far downstream of the die exit so that the flow is uniform.…”
Section: Problem Domain and Meshesmentioning
confidence: 99%
“…The polymer production process is mainly non-isothermal in nature, including heat transfer phenomena such as heating and cooling, e.g., in the injection molding [3,4] or extrusion [5][6][7][8] processes. Since the flow properties are strongly dependent on rheology and temperature, it is of great interest to understand and predict this type of heat transfer phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Ettinger gives an overview of work regarding shape optimization [13]. More recent research can be found in [24,31,22]. We note that all of this work is focused on shape optimization of the flow channel.…”
Section: Local Heating Of Extrudersmentioning
confidence: 99%
“…In the past, a number of design methods for polymer profile extrusion dies have been reported [4], which are primarily classified in two kinds of approaches for the extrusion die design [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rajkumar et al [5] adopted a novel method to balance the flow distribution in the extrusion die, and the cross-section geometry was divided into L and T shaped profiles. Yilmaz et al [7] proposed objective functions based on uniformity of velocity distribution at the die exit and adopted the Simulated Annealing-Kriging Meta-Algorithm for the optimization of extrusion die geometry.…”
Section: Introductionmentioning
confidence: 99%